Travel Preferences of the Zelenial Generation (Case Study of Five Vocational Schools in Medan) - Sumiati Sumiati; Emrizal Emrizal; Sumihar Sebastiana Sitompul (TechTalent & Business Review, 2026)
This research aims to determine the preferences of the millennial generation for traveling by conducting research on 5 Tourism Vocational Schools in the city of Medan. The number of respondents used in this research was around 400 people by distributing questionnaires using Google Form. The research method used is a mix method (qualitative and quantitative), using cross-tabulation analysis (quantitative) between the respondent's gender and travel preferences, while Milles and Hubberman (qualitative), using data collection patterns, reducing data and concluding data. with the results of the analysis of tourist destinations that are in demand, namely Lake Toba, around 46%, the preferred tourist facilities are free internet (74%), the ticket application is agoda.com (38%), tiket.com (30%), the preferred transportation is buses around 52%. %, the preferred activity is taking photos (52%), the historical tourist interest is Maimun Palace (33%), the reason for traveling is because of comfort (45%), the preferred content application is Tik Tok (42%), 38% expenditure of 125,000 – 150,000 , the most preferred culinary is regional food (54%), the type of tourism that is in demand is culinary tourism (28%), the preferred payment application is OVO (40%), the preferred accommodation is homestay (45%), and the type of maritime tourism that is preferred preferred, namely diving (45%), planning tourism products for Gen Z based on the 6 A pattern (Attraction, Accessibility, activity, amenities, ancelary, available package). The conclusion is that Gen Z's preferences based on gender have the same preferences in traveling, only a few things This is only different because the characteristics of Gen Z are the same, one of which is depending on the internet or the digital generation.